2007
DOI: 10.1016/j.ejcnurse.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and Relatives' Thoughts and Actions During and after Symptom Presentation for an Acute Myocardial Infarction

Abstract: Patients as well as relatives were insecure about AMI symptoms and how to act. All patients contacted a relative, who was more eager than the patient to seek help. Many preferred to go in their own car to the hospital, believing it to be faster than an ambulance. Information about AMI symptoms and recommended action should be given to the public and to AMI patients and their relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
(70 reference statements)
5
44
0
3
Order By: Relevance
“…When chest pain occurs, the majority of the participants would not recommend waiting before seeking medical care: however, in reality this is a common phenomenon [6][7][8][9]11,13,14,[17][18][19].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…When chest pain occurs, the majority of the participants would not recommend waiting before seeking medical care: however, in reality this is a common phenomenon [6][7][8][9]11,13,14,[17][18][19].…”
Section: Discussionmentioning
confidence: 97%
“…The questionnaire was developed by the investigators in collaboration with experts in the area: the questions were based on a previous qualitative study [13]. It was tested in a pilot study of 20-25 persons who fulfilled the criteria for participating in the patient and relative groups.…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Henriksson et al found that patients' disbelief and indecisiveness accounted for the highest PHDs. 13 Some patients had problems interpreting the symptoms, reflecting their lack of knowledge. The mismatch between patients' interpretation of symptoms and the progression of disease has been reported to be as high as 58%.…”
Section: Discussionmentioning
confidence: 99%